DEVELOPMENT OF UV SPECTROPHOTOMETRIC METHOD FOR THE DETERMINATION OF BENIDIPINE HYDROCHLORIDE BY USING QUALITY BY DESIGN (QbD) APPROACH - Kumar, Manish; Shukla, Ajay Kumar; Bishnoi, Ram Singh; Jain, C. P. (International Journal of Applied Pharmaceutics, 2018)
Objective: To develop a simple, rapid, accurate, robust and inexpensive spectrophotometric method for the estimation of benidipine hydrochloride by using quality by design (QbD)â€ approach. Methods: A UV spectrophotometric method was developed on Shimadzu UV-1800 double beam spectrophotometer using methanol as solvent and wavelength of 236 nm was selected as absorbance maxima (ðœ†max). Effect of input variables on spectrum characteristics were studied for the selection of critical parameters and proposed method was validated for various parameters like system suitability, linearity, precision, accuracy, detection limits and quantification limits as per the International Conference on Harmonization guidelines ICH Q2(R1). Results: Linearity of the method was found to be excellent over the concentration range 3 to 18 Âµg/ml with high correlation coefficient value of 0.9999. Limits of detection and quantification were found to be 0.20 Âµg/ml and 0.60 Âµg/ml respectively. The mean recovery was found to be 100.35 % with low percentage relative standard deviation (% RSD) value. The precision study also has shown low % RSD value (<1). No interfering peaks were observed during specificity studies. Conclusion: Obtained result indicated that the developed spectrophotometric method is robust and efficient for the determination of benidipine hydrochloride.